Absence of Bladder Outlet Obstruction Is an Independent Risk Factor for Prostate Cancer in Men Undergoing Prostate Biopsy. Issue 7 (February 2016) - Cormio, Luigi; Lucarelli, Giuseppe; Selvaggio, Oscar; Di Fino, Giuseppe; Mancini, Vito; Massenio, Paolo; Troiano, Francesco; Sanguedolce, Francesca; Bufo, Pantaleo; Carrieri, Giuseppe
Abstract : Abstract: The purpose of this study was to investigate the relationship between bladder outlet obstruction (BOO) and the risk of being diagnosed with prostate cancer (PCa). Study population consisted of 2673 patients scheduled for the first prostate biopsy (PBx). All patients underwent uroflowmetry before PBx; those with a peak flow rate (PFR) <10 mL/s were considered to have BOO. The incidence of PCa was 41.3% (1104/2673) in the overall population and 34.1% (659/1905) in patients with serum prostate-specific antigen (PSA) ≤ 10 ng/mL. Univariate and multivariate logistic regression analyses showed that patients with BOO had a significantly ( P < 0.0001) lower risk than those without BOO of being diagnosed with PCa (33.1% vs 66.9% in the overall population; 30% vs 70% in patients with PSA ≤ 10 ng/mL). As the presence of BOO was significantly correlated to a large prostate volume, another independent predictor of PBx outcome, we tested whether these parameters could be used to identify, in the subset of patients with PSA≤10 ng/mL, those who could potentially be spared from a PBx. If we would have not biopsied patients with BOO and prostate volume ≥60 mL, 14.5% of biopsies could have been avoided while missing only 6% of tumors. Only 10% of the tumors that would have been missed were high-risk cancers. In conclusion, in men undergoing PBx, the absence of BOO, as determined by a PFR ≥10 mL/s, is an independent risk factor for PCa. Our study provides ground for this simple, noninvasive, objective parameter being used, alone or in combination with prostate volume, in the decision-making process of men potentially facing a PBx.